Parametric oscillation of the prismatic beam with heredity of material - Da, Hoang Van (Vietnam Journal of Mechanics, 1983)
In this work the method set up the equation of motion of the prismatic beam under parametric excitation with regard to the heredity of material. The solution of this problem were constructed by means of average and asymptotic method. It is shown that heredity of material exerts its it influence on the amplitude of the oscillation as does viscous friction for a system with soft characteristics.